Pancreatic ductal adenocarcinoma: tumour regression grading following neoadjuvant FOLFIRINOX and radiation. Issue 1 (1st June 2020) - Neyaz, Azfar; Tabb, Elisabeth S; Shih, Angela; Zhao, Qing; Shroff, Stuti; Taylor, Martin S; Rickelt, Steffen; Wo, Jennifer Y; Fernandez-del Castillo, Carlos; Qadan, Motaz; Hong, Theodore S; Lillemoe, Keith D; et al.
Abstract : Aims: In the adjuvant setting, when compared to gemcitabine, patients with pancreatic ductal adenocarcinoma (PDAC) treated with FOLFIRINOX (Folinic Acid, Fluorouracil, Irinotecan, and Oxaliplatin) show superior survival. In this study, we quantitatively assess the pathological tumour response to chemoradiation in pancreatectomy specimens and reassess guidelines for tumour regression grading. Methods and results: We evaluated 92 patients with borderline resectable/locally advanced PDAC following pancreatectomy and neoadjuvant treatment with FOLFIRINOX and radiation. Demographic data, CAP tumour regression grade (TRG) and overall survival (OS) were recorded. A quantitative analysis of residual tumour was performed on the slide with the highest tumour burden to derive a tumour‐to‐tumour bed ratio. On univariate analysis, only lymph node status ( P = 0.043) and CAP TRG ( P = 0.038) correlated with OS. Sixteen per cent of patients showed a complete pathological response. The optimal tumour‐to‐tumour bed ratio cut‐point was 11.6%, and on a multivariate model was the only pathological parameter that correlated with OS ( P = 0.016) (hazard ratio = 2.27). Conclusions: The high proportion of patients with PDAC showing complete and near‐complete pathological responses supports the use of FOLFIRINOX and radiation in the neoadjuvant setting. Several traditional pathology parameters fail to predict OS in patients treated with chemoradiation, while a quantitative tumour‐to‐tumour bed ratio is a powerful predictor of OS. The data support a two‐tiered approach to TRG based on tumour‐to‐tumour bed ratio, and quantitative analysis merits further consideration.